Intestinal parasites in students of a public school in the city of São Mateus, Espírito Santo, Brazil - Pivetta, Heitor; Martins, Janaina dos Santos; Souza, Marco Antônio Andrade de (Brazilian Journal of Production Engineering, 2021)
The endemic character in some regions of Brazil for diseases caused by enteroparasites is still quite evident and few actions have been presented by government agencies to change this situation. Considering that the child population is the most affected by parasitological diseases, the present study analyzed stool samples from students in a public school in the city of São Mateus, Espírito Santo, Brazil and developed educational and awareness activities with the study population. The research was a descriptive nature, favoring an interpretative approach. Stool samples from participants were collected from April to June 2019, after signing a free and informed consent form by parents or guardians. The material was sent to Laboratório de Parasitologia e Hematologia Clínica of the Centro Universitário Norte do Espírito Santo, at the Universidade Federal do Espírito Santo and analyzed by the spontaneous sedimentation method. From a total of 52 collection vials distributed at the school among the individuals, who agreed to participate in the research, 22 samples (42.31%) were collected. Of these, 8 (36.36%) were positive for protozoan cyst and helminth eggs. Entamoeba coli (12.5%) commensal and Entamoeba histolytica/dispar (62.5%) and Trichuris trichiura (25%) parasites were the most prevalent. The results allow us to understand the relevance of the need for the application of health education measures and investments in the public service, in order to minimize the processes of parasitic transmission, especially in regions with social precariousness.
Keywords: Parasitology; Prevalence; Education; Child Population; Questionnaire